A física do estado sólido no Brasil: relações entre ciência, indútria e sociedade - Marzagão, Laércio Antonio (2018)
This work has two objectives. The first is to build a history of solid-state physics in Brazil according to three universes: that of the academy, that of industry and that of the state - whose presence in the creation of technology and science became remarkable since World War II. This history is recent, so interviews with representative people from these three universes in Brazil brought the substantial material for the construction of this history. The methodology adopted for the construction of this narrative is that of hybrid oral history. However, more than the isolated histories of these three universes, the interweaving of these three worlds was observed. Based on constructed history, the second objective is to identify the determinants that support the articulation between academia and industry and the resulting creation of wealth from knowledge. This work considers that the success of this articulation is context-dependent, which structure is defined by the theory of "diamond theory" by Michael Porter. The evaluation of the articulation between academia and industry between the years 1970 and 1990 exploits this same theory